Early Recurrent Inversion - A Case Report - Kabir, Nazneen; Islam, Ferdousi; Zannat, Fatematul; Razzak, Mollika (Bangladesh Journal of Obstetrics & Gynaecology, 2009)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <![endif]--> doi: 10.3329/bjog.v23i1.3056 Bangladesh J Obstet Gynaecol, 2008; Vol. 23(1) : 35-37